The Impact of Medicaid Expansion on Acute Diabetes Complication by Care Delivery Settings - Danielle Kulbak; Dang Dinh; Annie E. Larson; Andrew Suchocki; Rachel Springer; Miguel Marino; Jennifer E. DeVoe; Jun Hwang; Nathalie Huguet (Journal of Primary Care & Community Health)
Objective: This study evaluates whether gaining Medicaid following the Affordable Care Act (ACA) expansion led to changes in the rate of acute diabetes complications diagnosed in primary care settings, relative to in inpatient, emergency department (ED), or urgent care (UC) settings. Methods: This retrospective cohort study used Medicaid administrative claims data linked to electronic health records for 3767 patients, aged 19 to 64 years, who experienced acute preventable complications of diabetes between 2014 and 2019 diagnosed in inpatient, ED, UC, or primary care settings in the state of Oregon. These patients were classified as either continuously Medicaid-insured or having gained Medicaid. Results: Annual rates of acute complications diagnosed in primary care and inpatient/ED/UC settings increased for both continuously [Adjusted Rate Ratio (aRR) = 2.20, 95% CI = 1.65-2.91] and newly Medicaid-insured patients (aRR = 2.67, 95% CI = 2.05-3.47) after the ACA. Among newly Medicaid-insured, annual rates of abnormal blood glucose diagnosed in primary care settings significantly increased with time while those diagnosed in inpatient/ED/UC decreased (2014 vs 2016 aRR = 3.36, 95% CI = 1.60-7.09). Conclusion: We found a significantly greater rate of abnormal blood glucose diagnosed in primary care clinics among patients who gained Medicaid post-ACA and a corresponding decline in diagnosis in inpatient/ED/UC settings.